Constraining the bright-end of the UV luminosity function for z approximate to 7-9 galaxies: results from CANDELS/GOODS-South - Lorenzoni, S; Bunker, A; Wilkins, S; Caruana, J; Stanway, E; Jarvis, M (2013)
The recent Hubble Space Telescope near-infrared imaging with the Wide-Field Camera #3 (WFC 3) of the Great Observatories Origins Deep Survey South (GOODS-S) field in the Cosmic Assembly Near-infrared Deep Extragalactic Legacy Survey (CANDELS) programme covering nearly 100 arcmin2, along with already existing Advanced Camera for Surveys optical data, makes possible the search for bright galaxy candidates at redshift z≈7-9 using the Lyman break technique. We present the first analysis of z'-drop z≈7 candidate galaxies in this area, finding 19 objects. We also analyse Y-drops at z≈8, trebling the number of bright (HAB < 27 mag) Y-drops from our previous work, and compare our results with those of other groups based on the same data. The bright high-redshift galaxy candidates we find serve to better constrain the bright end of the luminosity function at those redshift, and may also be more amenable to spectroscopic confirmation than the fainter ones presented in various previous work on the smaller fields (the Hubble Ultra Deep Field and the WFC 3 Early Release Science observations).We also look at the agreement with previous luminosity functions derived from WFC3 drop-out counts, finding a generally good agreement, except for the luminosity function of Yan et al. at z≈8, which is strongly ruled out. ©2012 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.